Prediction of inpatient treatment duration for cataract patients according to their clinical and social status (Ukrainian Journal of Ophthalmology, 2026)
The purpose of the paper was to ground and to develop a model for predicting the duration of inpatient treatment of a cataract patient. We surveyed 60 cataract patients applied for surgical treatment in Hirchman Kharkiv City Clinic Hospital No 14.  A questionnaire consisted of several question pools answering which made it possible to assess a social state of patients, somatic and ophthalmic status, features of main disease as well as the duration of inpatient stay after surgery. If the duration of stay in hospital was 0-1 day, it was considered that one day surgery was performed.Fuzzy logic was used to design a model for prediction of inpatient treatment duration on the ground of findings of the questionnaire survey. A method of mountain clustering was used to obtain fuzzy rules.The most informative parameters for predicting the patient’s in-hospital stay duration after cataract surgery are age, finances, the number of concomitant somatic and eye diseases. To solve the tasks of clustering, optimizing and fuzzy inference, Scilab software package with sciFLT extension package can be used.
Keywords: cataract; outpatient treatment; prediction; fuzzy logic